LANGSTON HUGHES AND HIS POETRY - O`rmonxonova Zeboxon Xusniddinovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ANNOTATION: This article is about Langston Hughes who is American famous poet, dramatist, novelist, essayist. It describes his the way of life, famous poems, the way which he entered poetry and career. L.Hughes’s most well-known poems: “Let America be America again”, “ I, Too”, “Harlem”, “Dreams” and etc.